The impact of Benevolent Childhood Experiences on adult Flourishing: the mediating role of Light Triad traits - Landa-Blanco, Miguel; Herrera, Tatiana; Espinoza, Helen; Girón, Kilver; Moncada, Samantha; Cortés-Ramos, Antonio (Frontiers in Psychology, 2024)
The literature has well documented the relationship between Adverse Childhood Experiences, personality traits, and well-being. However, less is known about how Benevolent Childhood Experiences (BCEs) relate to “light” personality traits and Flourishing. The study analyzed the effects of BCEs on Flourishing, considering the mediator role of Light Triad traits (Kantianism, Humanism, and Faith in Humanity). The study used a quantitative methodology with a non-experimental, cross-sectional design; 410 Honduran adults responded to the survey, including questions regarding Light Triad personality traits, Flourishing, and BCEs. On average, respondents reported 7.34 BCEs. The number of reported BCEs did not vary significantly between men and women. However, specific BCEs were categorically associated with subjects’ sex. A higher proportion of men reported having at least one teacher who cared about the respondent, having opportunities to have a good time, and liking/feeling comfortable with oneself. Flourishing was significantly higher for participants who reported the presence of BCEs. The largest effect size was achieved for the difference in Flourishing scores between those who reported liking school as a child and those who disliked it. The number of Benevolent Childhood Experiences had a significant total and direct effect on Flourishing scores. Significant indirect effects were also identified. Faith in Humanity and Humanism, not Kantianism, mediated the relationship between BCEs and Flourishing. BCEs significantly explained all Light Triad traits. In conclusion, BCEs have significant direct and indirect effects on adult Flourishing; Faith in Humanity and Humanism mediate this relationship.